Body mass index (BMI) of adults: findings of the Malaysian Adult Nutrition Survey (MANS) - Md. Yusof, Azmi; Raib, Junidah; A., Siti Mariam; Md. Yusof, Safiah; S., Fatimah; Abdul Karim, Norimah; Poh, Bee Koon; Kandiah, Mirnalini; Mohd Shariff, Zalilah; Wan Muda, Wan Abdul Manan; Mohd Din, Siti Haslinda; A., Tahir (Nutrition Society of Malaysia, 2009)
The Malaysian Adults Nutrition Survey (MANS) was carried out between October 2002 and July 2003, involving 6,775 men and 3,441 women aged 18 - 59 years. Anthropometric assessment showed that the overall mean body weight and BMI were 62.65 kg (CI: 62.20, 63.09) and 24.37 kg/m2 (CI: 24.21, 24.53) respectively. Based on the WHO (1998) classification of BMI, 12.15% (CI: 11.26, 13.10) were obese (BMI > 30 kg/m2), and 26.71% (CI: 25.50, 27.96) overweight (BMI > 25-29.9 kg/m2). Significantly, more women were obese [14.66% (CI: 13.37, 16.04)] while significantly more men were overweight [28.55% (CI: 26.77, 30.40)]. Ethnicitywise, prevalence of obesity was highest among the Malays [15.28% (CI: 13.91, 16.77)] while overweight was highest for the Indians [31.01% (CI: 26.64, 35.76)]. Both obesity and overweight were highest among those aged 40-49 years. Obesity was highest for those whose household income was between RM1,500-3,500 while overweight was more prevalent for those whose household income exceeded RM3,500. The prevalence of overweight was highest for those with primary education [31.90% (CI: 29.21, 34.72)]. There was no significant urban-rural differential in both obesity and overweight. The study found 9.02% (CI: 8.82, 10.61) with chronic energy deficiency (CED) (BMI < 18.5 kg/m2). The prevalence of CED was relatively higher in the indigenous population (Orang Asli) [14.53% (CI: 5.14, 34.77)], subjects aged 18-19 years [26.24% (CI: 21.12, 32.09)], and with monthly household income of < RM1,500 [10.85% (CI: 9.63, 12.20)]. The prevalence of CED was not significantly different among the geographical zones and educational levels, and between urban/rural areas and sexes. The results call for priority action to address the serious problem of overweight and obesity among Malaysian adults as it poses a grave burden to the country's resources and development.